PERLINDUNGAN TERHADAP HAK-HAK PEREMPUAN PEKERJAMIGRAN INDONESIA DALAM UNDANG-UNDANG NOMOR 18 TAHUN 2017: PERSPEKTIF FEMINISME LEGAL THEORY - Husnah, Wabilia (Jurnal Hukum & Pembangunan, 2021)
Indonesian Migrant Workers (PMI) often experiencing physical, psychological, and sexual suffering. Indonesian Women Migrant Workers are also victims of trafficking. The implementation of Law of Indonesia No 18 Year 2017 is expected to protect Indonesian Women Migrant Workers. Thispaper will dissect the law through the perspective of the Feminist Legal Theory, to see whether the law has truly been able to fulfill all the rights of Indonesian Women Migrant Workers. This paper concludes that despite protecting Indonesian Women Migrant Workers, this law still feels gender blind. There are five weaknesses in this law, na mely: 1) not discussing the right to sexual and reproductive health; 2) does not discuss the protection of sexual and reproductive health; 3) there is no protection policy for women and children against sexual and reproductive health; 4) there is no training on the right to reproductive and sexual health for women; 5) there is no critical training and training on womens rights.